World Scientific Reference on Asia and the world economy - Whalley, John; Agarwal, Manmohan; Pan, Jiahua, 1957- (New Jersey : World Scientific, 2015)
'The dynamism in modern Asia, especially with the current revival in Japan, stands in sharp contrast to the situation in Europe. An in-depth understanding of what is happening in contemporary Asia is key to grasping opportunities that this dynamism creates for all. This multi-volume reference work consists of three up-to-date and comprehensive volumes on Asia and the world economy. It covers the most important aspects of the world economy as they pertain to Asia in the increasingly accelerating globalization process and is a must-have for anyone keen to understand Asia and the contemporary world. The three-volume set covers the climate change challenges and solutions from the Asian perspectives, focusing on both domestic arrangements and trade-based options, and discusses scenario analyses for future climate regimes; the sustainability of growth in the Indian economy determined by analyzing the role of economic, technological and environmental factors and lastly, the growth experiences and prospects of India and China'--
Volume 1. Sustainability of growth -- Volume 2. India and China : comparative experience and prospects -- Volume 3. Actions on climate change by Asian countries.
Includes bibliographical references and index.
Keywords: Economic development -- Asia; Sustainable development -- Asia; Globalization -- Asia; Climatic changes -- Economic aspects -- Asia; Asia -- Foreign economic relations